Utilization of TOGA to Reduce the Risk of Hypertension in Cibiru Wetan Village - Jajang Japar Sodik; Fenti Fatmawati; Mia Nisrina Anbar Fatin; Wempi Budiana (Warta Pengabdian Andalas, 2025)
Community service activities in Cibiru Wetan Village, Bandung Regency have been carried out by lecturers and students of the Faculty of Pharmacy, Bhakti Kencana University (BKU) with partners, namely PKK Cibiru Wetan and Cibiru Wetan Health Center. Activities carried out in November include health screening (blood pressure, blood sugar, uric acid and total cholesterol checks), education on hypertension and the benefits of TOGA, training in processing medicinal plants such as ginger, Kaempferia galanga, and Curcuma into ready-to-consume herbal products, distribution of booklets on practical guidelines for the use of TOGA. This activity involves BKU lecturers from various expertise groups such as Pharmacology & Clinical Pharmacy; Pharmacy and Pharmaceutical Technology; General Pharmacy and Pharmacists; Pharmaceutical Biology.